To do or not to do: prolapsed, bleeding, rectal polyp, a dilemma in austere circumstances. Issue 10 (27th October 2020) - Pandya, Bharati; Golmei, Jason; Henriques, Merlyn S; Dawar, Anil
Abstract: Polyps are defined as abnormal growth of tissue from a mucosal surface. Rectal polyps are the most common (2%) cause of gastro-intestinal bleed in children below 10 years. In adults, a rectal polyp presenting as an emergency with irreducible prolapse and massive bleeding causing severe anemia is seldom seen. We present one such case in which surgery was performed under austere circumstances before any investigations, as a life saving measure.